2016
DOI: 10.1098/rsif.2016.0554
|View full text |Cite
|
Sign up to set email alerts
|

Structured free-water clusters near lubricating surfaces are essential in water-based lubrication

Abstract: Water-based lubrication provides cheap and environmentally friendly lubrication and, although hydrophilic surfaces are preferred in water-based lubrication, often lubricating surfaces do not retain water molecules during shear. We show here that hydrophilic (428 water contact angle) quartz surfaces facilitate water-based lubrication to the same extent as more hydrophobic Si crystal surfaces (618), while lubrication by hydrophilic Ge crystal surfaces (448) is best. Thus surface hydrophilicity is not sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The water stretching band ( Fig. 4d) was decomposed into two components for bound (around 3,308 cm Ϫ1 ) and free (around 3,469 cm Ϫ1 ) water (14,15). Absorption band areas and IR absorption band wavenumbers represent the amount and bond stiffness of the corresponding molecules, respectively, and have been plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The water stretching band ( Fig. 4d) was decomposed into two components for bound (around 3,308 cm Ϫ1 ) and free (around 3,469 cm Ϫ1 ) water (14,15). Absorption band areas and IR absorption band wavenumbers represent the amount and bond stiffness of the corresponding molecules, respectively, and have been plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between the protective effect of IR, interfacial water structuring and presence of the strongly water-holding residues was demonstrated by results of our previous study [23]. That study indicated that IR-induced increase in cooperativeness and strength of H-bonds of protein interfacial water correlated with the protonation state of the basic amino-acid residues and that enhanced structuring of the hydration shell (acting as lubricant [69,70]) protected proteins from non-specific aggregation in solution. In this context it is interesting to consider different structural response of BSA and OVA to IR light (Fig.…”
Section: Ir Protection From Surface Denaturationmentioning
confidence: 78%
“…Moreover, the nonpolar groups in the molecule show certain lateral cohesion; 26 thus, the adsorption film with suitable strength and thickness is necessary, which signifies the limitation of the ILs−water solubility and the balance between solubility and adsorption. In addition, the interaction between water and ILs is mainly manifested in the hydrolysis stability and salting-out effect, 27 as well as various ILs behave differently in aqueous lubrication systems. Consequently, an intensive analysis of the interfacial competitive adsorption behavior and tribochemical mechanisms of IL water-based lubricating systems is urgently desired and extremely beneficial.…”
Section: ■ Introductionmentioning
confidence: 99%